Adherence to Iron-Folic Acid Supplementation and Associated Factors among Antenatal Care Attendants in Public Health Institutions: The Case of Borena District, Amhara, Ethiopia: Cross-Sectional Study - Ali, Suleyiman Hassen; Wolka, Eskinder; Liben, Misgan Legesse (International Journal of Child Health and Nutrition, 2022)
Introduction: Globally, iron deficiency is estimated to be responsible for half of all anemia cases. The reduction of iron deficiency anemia in pregnant women relies largely on their adherence to IFA supplementation. This study aimed to assess the factors associated with adherence to IFA supplementation among women attending antenatal checkups at health centers in Borena district, Ethiopia. Methods: Institution-based cross-sectional study design was conducted on 348 pregnant women. The data were analyzed using SPSS version 20. Variables with a p-value of ≤0.2 in the univariable logistic regression analysis were included in the multivariable analysis. Adjusted odds ratio with 95% confidence interval was reported, and variables with p<0.05 were considered statistically significant. Result: A total of 340 pregnant women were enrolled. The study revealed that 45.6% (95% CI: 40.27, 50.92%) of women adhered to the IFA supplement use. Women of husbands with primary education [AOR: 1.95; 95% CI: 1.07, 3.57] and who had taken IFA for two months [AOR: 2.81; 95% CI: 1.37, 5.79] were positively associated with adherence to IFA supplementation. However, women with a previous history of abortion [AOR: 0.16; 95% CI: 0.50, 0.53], who had disease other than anemia [AOR: 0.48; 95% CI: 0.28-0.79] and lack of family support [AOR: 0.12; 95% CI: 0.04, 0.39] were less likely to adhere to the supplement. Conclusion: This study revealed that nearly nine in twenty women adhered to the IFA supplement. Therefore, strengthening nutritional counseling, health education, and information on iron-folic acid supplementation in a health institution is important to improve adherence.